2016
DOI: 10.2298/jsc150706092w
|View full text |Cite
|
Sign up to set email alerts
|

Degradation kinetics of fisetin and quercetin in solutions affected by medium pH, temperature and co-existed proteins

Abstract: The impacts of medium pH, temperature and co-existing proteins on the degradation of two flavonoids, fisetin and quercetin, were assessed in the present study using a spectroscopic method. Based on the measured degradation rate constants (k), fisetin was more stable than quercetin in all cases. Increasing the medium pH from 6.0 to 7.5 at 37 °C enhanced the respective k values of fisetin and quercetin from 8.30×10-3 and 2.81×10-2 to 0.202 and 0.375 h-1 , respectively (p < 0.05). In comparison with their degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 25 publications
10
46
0
Order By: Relevance
“…On the other hand, quercetin showed a lower analytical response at pH 7.4, despite the acidification carried out during sample preparation; thus, it was necessary to define an independent regression model for this compound in each pH condition. The lower response of quercetin at alkaline pH could be a consequence of the poor stability of the compound as was confirmed experimentally (Figure , Table ) and supported by other authors …”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, quercetin showed a lower analytical response at pH 7.4, despite the acidification carried out during sample preparation; thus, it was necessary to define an independent regression model for this compound in each pH condition. The lower response of quercetin at alkaline pH could be a consequence of the poor stability of the compound as was confirmed experimentally (Figure , Table ) and supported by other authors …”
Section: Discussionsupporting
confidence: 77%
“…The reaction was shown to be pH-depended within a pH range from 4.1 to 7, exhibiting a linear correlation between k and pH. Such a phenomenon was further confirmed by more recent examinations, which showed a pH-depended degradation of quercetin within a narrower pH region of 6 to 7.5, at 37 • C, but also a temperature-dependent increase in k, within a range of 37 to 65 • C [20]. In the same line, latter investigations showed that Cu 2+ -induced quercetin oxidation at pH 8 and 97 • C also displayed first-order kinetics, with k being linearly correlated [14].…”
Section: Preliminary Oxidation Kinetics and Temperature Effectssupporting
confidence: 67%
“…An example is the biochemical transformation of flavylium cation of anthocyanidin to less stable chalcone and carbinol pseudobase forms even at near-neutral pH 45 , which eventually leads to degradation of anthocyanin 42,46 . Similarly, flavonols, such as quercetin, have been reported to undergo oxidation, hydroxylation, and ring cleavage at medium pH values in a time-dependent manner resulting to the formation of complex product profiles 47 . The low chemical stability of these compounds, as a function of their chemical structure, in the mild alkaline pH condition of the small intestine could cause their degradation and inactivity 46 .…”
Section: Discussionmentioning
confidence: 99%